Perancangan Interior Sentra Kuliner Khas Sulawesi Selatan di Makassar - Yenmy Liechandra; Stephanus P Honggowidjaja (Intra, 2016)
As one of the major provinces in Indonesia, South Sulawesi has many tourist destinations, in particular culinary tourism. Wealth ideals and sense embodied in a wide variety of culinary make the typical cuisine of South Sulawesi is renowned as one of Indonesian cuisine. This became the advantages to attract tourists, both local and foreign tourists to learn more about Indonesia, especially South Sulawesi. However, it is still less available dining facilities that provide unique culinary. The typical cuisine is available in several different dining venues or separately. To facilitate the tourists to try and taste the flavor of Sulawesi’s cuisine, takes an area or dining facilities where in it provides a variety of unique culinary South Sulawesi. To introduce South Sulawesi to tourists can be realized not only from the culinary aspect, but also from the interior design. Interior reflecting regional locality. Although the design follows the trend of the times now, but still blend with the local environment. The method used is a methodology of design thinking, which involves the process of collecting data, analysis, find the concept to final design. Modern traditional design concept is expected to attract tourists and become an icon of culinary centre in Makassar.